Great world religions Hinduism - Muesse, Mark William 1957-; Teaching Company (Chantilly, Virginia The Teaching Company, 2003)
Provides an overview of Hinduism and discusses why Hinduism is perhaps the most diverse religion of all. Covers topics such as arranged marriages and the caste system, the Indus Valley Civilization, the sacred writings in the Vedas, the Bhagavad-gita, and the Upanishads, ritual purity rites, the Aryan language of Sanskrit, and Hinduism's rejection of the notion that there is but one path to the divine. Introduces Hinduism's wealth of gods, terms, and practices, such as Krishna, karma, guru, and yoga.
Lecture 1. Hinduism in the world and the world of Hinduism -- Lecture 2. Early cultures of India -- Lecture 3. World of the Veda -- Lecture 4. From the Vedic tradition to classical Hinduism -- Lecture 5. Caste -- Lecture 6. Men, women, and the stages of life -- Lecture 7. Way of action -- Lecture 8. Way of wisdom -- Lecture 9. Seeing God -- Lecture 10. Way of devotion -- Lecture 11. Goddess and her devotees -- Lecture 12. Hinduism in the modern period.
Lecture transcript and course guidebook published to accompany DVD and and videotapes with the same title.
Includes bibliographical references.
Keywords: Vedas; Upanishads; Bhagavadgītā; Hinduism; Indus civilization; Indo-Aryans.; India -- Religion